Análise técnico-econômica entre soluções de distúrbios de qualidade de energia elétrica - Bruna Rafaela Penido Conrado (2020)
This dissertation aims at proposing a computational tool able of performing a technicaleconomic analysis between the different topologies of compensators used to mitigate the excessive circulation of reactive power, harmonics and unbalance load in industrial environments. Problems caused from low levels of power quality indices, such as shortened equipment life, overheating devices and motor vibration, high current value through the neutral conductor, resonances, error in converter control, mistriggering of protections, can be mitigated. Therefore, it is necessary to install different mitigating equipment available on the market, such as active filters, passive filters and static reactive compensators. The choice of the appropriate compensator to mitigate the electrical disturbance, which keeps the power quality indicators within the limits established by national and international standards and which is economically viable is an important task for industrial consumers. Thus, a tool is developed capable of analyzing the cost versus benefit of some solutions, and their compensation associations, verifying the economic benefits of installing the compensator and the financial attractiveness of its implementation. In order to evaluate this tool, considering real operating conditions, case studies are carried out. As a result, the consumer is informed whether, within a given period of time, the best solution will be paying the consumption and demand for surplus reactive energy in the electric bill or to investing in compensation equipment.